Peran Profitabilitas dalam Memediasi Pengaruh Likuiditas dan Struktur Modal Terhadap Nilai Perusahaan - Sinta Nuriyah; Sugeng Priyanto (MANAJEMEN, 2026)
This study aims to determine the effect of liquidity and capital structure on Company Value with profitability as an Interverning variable in telecommunication sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2024. The sample of this study was 15 telecommunication sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. In this study, path analysis was carried out assisted by the SPSS version 22 program and Microsoft Excel 2019. The results of the study show that 1) Liquidity has a significant effect on Profitability, 2) Capital Structure has a significant effect on Profitability, 3) Profitability has a significant effect on Company Value, 4) Liquidity has a significant effect on Company Value, 5) Capital Structure has a significant effect on Company Value, 6) Profitability is unable to mediate the effect of Liquidity on Company Value, 7) Profitability is unable to mediate the effect of capital structure on Company Value.